Field performance, yield components and nitrogen utilization efficiency of potato plants grown from hydroponic small tubers - Chang, Dong Chil; Hur, On Sook; Park, Choun Soo; Kim, Sung Yeul (Horticulture, environment and biotechnology, 2011)
Despite the available reports on hydroponic potato production, little is known about its field establishment, yield components and efficiency of nitrogen (N) use from small hydroponic tubers (HT) planted in fields. Three sizes of HT (0.7 g, 5 g, and 10 g) and conventional cut seed tubers (CT) of about 40 g of medium-early maturity cultivar ‘Superior’ were planted at the Highland Agriculture Research Center, Pyeongchang, Korea, on 20 May 2005 and 23 May 2006, and their field performances were compared. Increasing seed size resulted more emergence, faster shoot growth soon after emergence, higher N utilization efficiency (plant dry matter accumulation / plant N accumulation), higher tuber growth rate (TGR) and dry matter production, and higher fresh tuber yields. The first tuber formation and bulking were observed in CT plants followed by HT plants of 5 g and 10 g. The time to tuber formation and tuber bulking in 0.7 g HT plants was the longest and delayed by 6 or 8 days compared to CT plants. Accumulation of tuber dry matter increased linearly from the period of tuber formation to near harvest. During the period, increasing seed size gave a significant increase in dry matter production in tubers. Tuber fresh yield of 0.7 g HT plants was 55% of that of CT plants, while those of larger HT (5 g and 10 g) plants were 75% and 80%, respectively. The results suggested the potential of using HT (5 to 10 g) for direct field planting.